Empowerment program through project-based learning and assessment to enhance teachers' scientific writing - Hilarius Jago Duda; Imanuel Sairo Awang; Beni Setiawan; Hendrikus Julung (University of Merdeka Malang, 2024)
The traditional lecture-based learning followed by questions or assignments from the teacher, as observed in partner schools, often fails to fully empower students' abilities. Research conducted by the PKM team has shown that practicum-based and project-based learning can effectively enhance various student skills, including cognitive abilities, critical thinking, creativity, process skills, and attitudes. The Community Empowerment Program (PMP) aims to empower and enhance the knowledge and skills of teachers in developing project-based learning tools and assessments, creating learning products, as well as writing and publishing scientific papers. This activity involves socialization, training, mentoring, and review of project-based learning and assessments, as well as article writing and publication using PTK methodology for science teachers. Participants in the program are science teachers from schools in the Sepauk sub-district, Sintang, West Kalimantan. The program was implemented from June to September 2024. The results of the activities indicate that teachers actively and enthusiastically participated in the socialization, training, mentoring, and guidance sessions. The products generated from the PKM activities were 90 percent successful, and there was an 80 percent increase in teacher empowerment through these activities.